(untitled) (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2018)
In the article there are theoretical and experimental investigations presented with regards to determination of optimal parameters of straight-flow turbine for damless hydro power stations. The goal for conducting theoretical and experimental investigations is to increase electric power of hydro turbines.Upon the results of the theoretical research, the amount of blades located in the rotor of the hydro turbine was calculated. The measures of blade thickness were undertaken depending on their overall number. To define the most optimal profile (shape), different blade profiles located in the rotor of the hydro turbine were preliminarily put into the COMSOL Multiphysics software. Regarding the blade defined as the most optimal in accordance with its angle of location, calculations of inner flown water velocity changes along with water pressures experienced by the blade were produced. As a result of the research outcomes, the most optimal angle for blade location was calculated, it was possible to observe the processes of vortex and cavitation during water flows through the blade. The calculations with regards to incompressible liquids were measured with the help of COMSOL Multiphysics software through application of Direct Numerical Simulation (DNS) method on the base of Navier-Stokes equation. The experimental investigations were conducted in the Laboratory of Hydro Power Stations and Hydro Power Constructions within the Kazakh Scientific Research Institute of Energy named after Sh. Chokin. In the framework of the experimental investigations there were defined a number of revolutions per minute with regards to the rotor of the hydro turbine depending on changes of water withdrawals as well as the amount of electric power generation.